Properties of Ga-containing pentasils in aromatization of lower alkanes after repeated reaction-regeneration cycles; Russian Journal of Applied Chemistry; Vol. 68, iss. 5 - Vosmerikov A. V. (1995, 1995)
Variation of catalytic and acidic properties of gallium-containing zeolite catalysts in aromatization of Lower alkanes after several reaction-regeneration cycles has been examined. The catalytic activity only slightly decreases from cycle to cycle, and a relatively large number of oxidative regenerations can be performed.